Driving e-loyalty in e-retailing: the role of e-service quality, e-satisfaction, and e-trust in Tokopedia - Nadya Zulkarnain; Siti Rahayu; Adi Tedjakusuma (Faculty of Business and Economics, University of Surabaya, 2025)
The rapid development of the digital era has made e-retailing, particularly in Indonesia, a popular choice for online shopping. A critical factor influencing an e-retailing company's value is e-service quality. This study aims to assess the impact of e-service quality, measured through efficiency, privacy, reliability, emotional benefits, and customer service, on attitudinal and behavioral loyalty, with e-trust and e-satisfaction serving as mediators. Using purposive sampling, data were collected from 230 respondents across Indonesia through Google Forms. The analysis, conducted via Structural Equation Modeling (SEM) with SPSS AMOS 23, revealed that efficiency, emotional benefits, and customer service positively affected e-satisfaction and e-trust, which in turn influenced both types of loyalty. However, privacy, reliability, and the emotional benefits dimension did not have significant effects on e-satisfaction or e-trust. These findings offer valuable insights for improving Tokopedia’s e-service quality to enhance customer loyalty and performance.